The art of Mehndi - Batra, Sumitra (Carlton Books, 2013)
The Art of Mehndi is the definitive style guide to the fascinating ancient art form of henna body decoration, covering everything from the historical, symbolic and spiritual aspects of henna to its adoption by the West as a way of decorating the body without the permanence of traditional tattoos. Sumita Batra, a leading mehndi artist.